KONTRIBUSI DAN IMPLIKASI TEORI INSTRUKSIONAL - Salamah, Salamah (Jurnal Inovasi Pendidikan, 2010)
Instruction is a set of events which affect learners in such a way that learning is facilitated. The objectives of the instruction are achieved by affecting learners to make them able to learn; so that the instruction process should be purposively controlled and aimed at. O ensure effective and efficient instruction, there are three affecting variables of instruction, namely, condition of instruction, methods of instruction, and outcomes of instruction. The application of various instructional theories in education technology involves 8 (eight) theories. They are: Programmed Instruction theory, Instructional Capability theory, Algorithmic-Heuristic theory, Structural Learning theory, Theory of Inquiry Teaching, Component Display Theory, Elaboration theory, and Discovery Learning theory.